INNOVATSION BOSHQARISHNING MAKTABGACHA TA’LIM TASHKILOTLARIDAGI ZAMONAVIY SHARTLARI - Ergasheva Barno Nuriddin qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Innovative management and planning of preschool education organizations is one of the urgent tasks of our time. The article expresses opinions on new innovative methods of leadership and management in preschool educational organizations.